Cellular and molecular events leading to mitochondrial toxicity of 1-(2-deoxy-2-fluoro-1-beta-D-arabinofuranosyl)-5-iodouracil in human liver cells. - Cui, L (1995)
We have explored the mechanism(s) related to FIAU-induced liver toxicity, particularly focusing on its effect on mitochondrial function in a human hepatoma cell line-HepG2. The potential role of FMAU and FAU, metabolites detected in FIAU-treated patients were also ascertained. FIAU and FMAU inhibited cell growth and were effectively phosphorylated. A substantial increase in lactic acid production in medium of cells incubated with 1-10 microM FIAU or FMAU was consistent with mitochondrial dysfunction. Slot blot analysis demonstrated that a two week exposure to 10 microM FIAU or FMAU was not associated with a decrease in total mitochondrial (mt) DNA content. However, FIAU and FMAU were incorporated into nuclear and mtDNA and relative values suggest that both compounds incorporate at a much higher rate into mtDNA. Electron micrographs of cells incubated with 10 microM FIAU or FMAU revealed the presence of enlarged mitochondria with higher cristae density and lipid vesicles. In conclusion, these data suggest that despite the lack of inhibition of mtDNA content, incorporation of FIAU and FMAU into mtDNA of HepG2 cells leads to marked mitochondrial dysfunction as evidenced by disturbance in cellular energy metabolism and detection of micro- and macrovesicular steatosis.